ANALYSIS OF IODINE CONTENT IN TABLE SALT - Eka Ratri Noor Wulandari (Program Pendidikan Vokasi Universitas Indonesia, 2017)
Iodine is essential nutrients for human body. It is needed by thyroid gland to produce thyroxine hormone. Human body cannot produce iodine by itself. There are some sources of iodine in food such as seafood, milk, egg, fruit and vegetable that can be consumed to fulfill the daily needs. Table salt is one of iodine’s source that routinely consumed, based on SNI No. 3556:2010, it has to be fortified by potassium iodate of 30-80 ppm. Lack of iodine intake will lead a disorder called Iodine Deficiency Disorders (IDD) which generally manifested as mumps. In this research, the analysis of iodate content in table salt was done by formation of blue I2-starch complex. The several optimum conditions showed for this measurement such as maximum wavelength, type and concentration of acid, and complex stability time. Based on commercial table salt sample analysis, showed that only 50% of our sample contain suitable amount of iodine while the others contains lower or almost no iodine. Keyword; table salt, iodine, iodate, I2-starch complex